A case of incarcerated umbilical hernia in a 9-year-old child and review article on pediatric umbilical hernia - Aleksandar Stepanovski; Lazo Jovcheski; Slavica Litajkovska; Andrijana Andreevska Stepanovska (Elsevier, 2022)
Umbilical hernia in children is a relatively common condition with a higher prevalence in premature, low-birth weight and black children. By contrast, complicated umbilical hernia rarely occurs. Early recognition of this condition is essential in order to prevent potential ischemic consequences. Most authors recommend a conservative stance of watchful waiting for the uncomplicated pediatric umbilical hernias up to the age of 4 years, with an emergent surgical correction in complicated cases. We report an uncommon case of a 9-year-old male who presented with sharp abdominal pain, irreducible umbilical mass, and vomiting following strenuous physical activity. Additionally, we provide insight on the current knowledge of pediatric umbilical hernia with a particular focus on its complications.